The Effect of the Number of Rotations of the Saw Cylinder on the Quality Indicators of the Seed - J.G. Gayratov; R.K. Djamolov (Genius Journals, 2023)
The article presents the results of the effect of the number of revolutions on the seed parameters, using improved constructions of saw cylinders instead of metal brush cylinders from the main working parts of the 1LB linter without the grate, which implements the first stage of the two-stage dehairing technology of cotton seed
Keywords: Saw; cylinder; metal brush; linter without grate